Pesticides Ecotoxicological Risk Assessment for Surface Waters in the Cotton Growing Area Around the Bala’s Hippopotamus Pond Biosphere Using PIRI Method - Bayili, Bazoma; Ouedraogo, Richard; Sidibe, Hassane; Ilboudo, Sylvain; Ouedraogo, Georges Anicet (European Scientific Journal, ESJ, 2021)
Pesticides residues are frequently found in the environment far from the original point of their application. Besides the desired effects of pest control, non-target organisms, soil and water are contaminated by the pesticides. This paper presents results on the impact of these xenobiotics used in cotton cultivation on River "Wolo" environment in Burkina Faso by using the Pesticide Impact Rating Index (PIRI) software package. The assessment was based on the assumption of three scenarios taking into account the organic matter content of the soil and the presence of a buffer zone. Pesticides properties and use data, and data on the physical environment, were also used. Considering the worst case (scenario 2), diuron, haloxyfop-R-methyl, glyphosate and nicosulfuron were the most mobile. Diuron was classified as the most toxic pesticide to Scenedesmus quadricauda. Toxicity to Daphnia magna was extremely high with chlorpyrifos ethyl, very high with betacyfluthrin, deltamethrin, lamda-cyalothrin and high with flubendiamide. For Oncorhynchus mykiss, it was beta-cyfluthrin, deltamethrin and lamdacyhalothrin that caused a very high risk and chlorpyrifos ethyl and indoxacarb a high risk. For all pesticides, the risks are reduced overall depending on the width of the buffer zone and the organic matter content of the soil. The use of a pesticide in a given location must take into account its ecotoxicological impact on the surrounding ecosystem. Tools such as PIRI, could be used for the selection of pesticides to be used. Also, environmental parameters such as buffer zone and organic matter content should be used by farmers to limit the mobility of pesticides to water.